The endoplasmic reticulum HSP40 co‐chaperone ERdj3/DNAJB11 assembles and functions as a tetramer - Chen, Kai‐Chun; Qu, Song; Chowdhury, Saikat; Noxon, Isabelle C; Schonhoft, Joseph D; Plate, Lars; Powers, Evan T; Kelly, Jeffery W; Lander, Gabriel C; Wiseman, R Luke (The EMBO journal, 2017)
ERdj3/DNAJB11 is an endoplasmic reticulum (ER)‐targeted HSP40 co‐chaperone that performs multifaceted functions involved in coordinating ER and extracellular proteostasis. Here, we show that ERdj3 assembles into a native tetramer that is distinct from the dimeric structure observed for other HSP40 co‐chaperones. An electron microscopy structural model of full‐length ERdj3 shows that these tetramers are arranged as a dimer of dimers formed by distinct inter‐subunit interactions involving ERdj3 domain II and domain III. Targeted deletion of residues 175‐190 within domain II renders ERdj3 a stable dimer that is folded and efficiently secreted from mammalian cells. This dimeric ERdj3 shows impaired substrate binding both in the ER and extracellular environments and reduced interactions with the ER HSP70 chaperone BiP. Furthermore, we show that overexpression of dimeric ERdj3 exacerbates ER stress‐dependent reductions in the secretion of a destabilized, aggregation‐prone protein and increases its accumulation as soluble oligomers in extracellular environments. These results reveal ERdj3 tetramerization as an important structural framework for ERdj3 functions involved in coordinating ER and extracellular proteostasis in the presence and absence of ER stress. Synopsis The HSP40 co‐chaperone ERdj3/DNAJB11 coordinates endoplasmic reticulum (ER) and extracellular proteostasis. Cryo‐EM shows ERdj3 to adopt a native tetramer form that is required for efficient substrate binding and for maintaining secretory proteostasis during ER stress. The ER HSP40 co‐chaperone ERdj3 assembles into a native tetramer. Electron microscopy reveals the domain architecture of the ERdj3 tetramer. Disruption of ERdj3 domain II renders ERdj3 a stable dimer. Disruption of the ERdj3 tetramer decreases substrate binding. Dimeric ERdj3 shows impaired capacity to regulate secretory proteostasis during ER stress. Graphical Abstract CryoEM reveals that co‐chaperone ERdj3 displays an unusual tetramer organization, which is required for efficient substrate binding and for maintaining secretory proteostasis during ER stress.